Software for developing digital twins of agricultural machinery working bodies - D. A. Mironov; D. V. Popov; R. K. Rasulov; A. K. Lamm (Сельскохозяйственные машины и технологии)
Digital twins, as virtual models of physical entities, are becoming vital in modeling various objects and phenomena in the modern world. In the agricultural sector, their role is particularly crucial, since digital twins facilitate not only the analysis of soil, climate, yield, and plant data but also the forecast of changes in these parameters. Accumulating and analysing vast amounts of information, digital twins help optimize the use of resources such as water, fertilizers, and pesticides, which in turn leads to increased yields and reduced costs. Moreover, digital twins enable the automation of many processes in agriculture, including the management of agricultural machinery and equipment. They provide the capability for more precise and efficient control of units such as tractors and combines, and also assist in predicting and preventing equipment failures, thereby reducing time and financial losses. (Research purpose) The paper aims to analyze software products used in the design and development of digital twins.(Materials and methods) The paper evaluates various software programs, selected based on their functionality range and compatibility with other systems.(Results and discussion) The paper assesses the effectiveness of each program in fulfilling its intended tasks. The provided examples highlight distinct features of each software type. Criteria for program selection were formulated. (Conclusions) The findings delineate the characteristics and functionalities of the evaluated software products, thereby determining their functional capabilities. Necessary requirements were defined to facilitate decision-making in selecting programs with similar functionality.